Perbandingan Asas Kebebasan Berkontrak Antara Kontrak Pemerintah dan Kontrak Swasta - Sandra Suryani; Sami’an Sami’an; Sarwono Hardjomuljadi (Jurnal Impresi Indonesia, 2026)
The principle of freedom of contract is a fundamental principle in contract law which gives parties the authority to determine whether they will make an agreement, with whom the agreement is made, as well as the content and form of the agreement. This principle is rooted in the idea of ??autonomy of will which places contracts as the result of free agreement between the parties. However, in practice, the principle of freedom of contract is not applied uniformly to all types of contracts. Differences in the character of the parties, the purpose of the contract, and the interests protected by law cause variations in restrictions on freedom of contract, especially between government contracts and private contracts. Government contracts, even though they are in the form of agreements, cannot be separated from the state's function as organizer of public interests, so that freedom of contract in them experiences stricter restrictions. On the other hand, private contracts provide a wider space for freedom, although in practice they still face limitations due to the unequal bargaining positions of the parties. This research aims to analyze the concept of the principle of freedom of contract and compare its application in government contracts and private contracts in order to assess the relevance and legitimacy of this principle in modern contractual practice.